Optimizing MultiStack Parallel (MSP) Sorting Algorithm - Apisit Rattanatranurak; Surin Kittitornkun (Journal of Mobile Multimedia, 2021)
Mobile smartphones/laptops are becoming much more powerful in terms of core count and memory capacity. Demanding games and parallel applications/algorithms can hopefully take advantages of the hardware. Our parallel MSPSort algorithm is one of those examples. However, MSPSort can be optimized and fine tuned even further to achieve its highest capabilities. To evaluate the effectiveness of MSPSort, two Linux systems are quad core ARM Cortex-A72 and 24-core AMD ThreadRipper R9-2920. It has been demonstrated that MSPSort is comparable to the well-known parallel standard template library sorting functions, i.e. Balanced QuickSort and Multiway MergeSort in various aspects such as run time and memory requirements.
Keywords: Parallel Computing and Optimization Techniques